Independent Predictors of Erectile Dysfunction in Type 2 Diabetes Mellitus: Is It True What They Say about Risk Factors?. (27th August 2012) - Sharifi, Faranak; Asghari, Mohammad; Jaberi, Yahya; Salehi, Oveis; Mirzamohammadi, Fatemeh
Abstract : Introduction . The aim of this study was to evaluate the independent predictors of ED in adult men with type 2 diabetes mellitus (T2DM). Methods . We have recruited 200 T2DM patients referred to our center between March 1, 2009 and March 1, 2010. All the patients were scored with the International Index of Erectile Function (IIEF)-5 questionnaires. Contribution of age, body mass index (BMI), smoking, blood pressure, lipid profile, fasting plasma glucose (FPG), glycosylated hemoglobin (HbA1c), free testosterone concentration, and duration of diabetes to risk of ED were evaluated. Results . Of 200 men with T2DM, 59.5% had ED (95%CI: 52%–67%). A negative significant correlation was found between potency score and HbA1c ( r : 0.20, P : 0.01), FPG ( r : 0.17, P : 0.03) and SBP ( r : 0.18, P : 0.02) but not between other risk factors such as lipid profile, BMI, and serum testosterone level. By using multivariate logistic regression analysis, we found out that the only two independent predictors of ED in these group of patients are age (OR: 2.8, P : 0.01), and taking calcium channel blockers (CCB) (OR: 4.1, P : 0.01). Conclusions . Aging and taking CCB were the only two major predictors for ED but surprisingly other metabolic or sexual covariates in this study did not have predictive value for ED risk in T2DM patients.